Empirical Study on the Antenna-Dependent Accuracy of Continuous- Wave Radars - Tegowski, Bartosz; Schulz, Bjorn; Koelpin, Alexander (2024 15th German Microwave Conference, GeMiC 2024, 2024)
The impact of antennas on the accuracy of continuous-wave radar systems is examined in this contribution. Due to its own radar cross section (RCS), the radar antenna redirects a fraction of the incident field, originally scattered by the target, towards the latter. This generates virtual targets, which impair the accuracy of relative distance measurements. The associated errors are empirically studied for a selection of horn antennas and patch antenna arrays by measurements with a vector network analyzer in the 24-GHz ISM band. The errors vary with the antenna type and can be up to several hundreds of micrometers. It is shown that a specific reduction of the antenna RCS improves the accuracy.
Created from Fastlane, Scopus look-up
Keywords: Accuracy; continuous-wave (CW) radar; horn antenna; interferometric radar; patch antenna array; radar cross section (RCS)